Convective heat transfer coefficients of a naturally ventilated building integrated photovoltaic (BIPV) system - Kalogirou, Soteris A.; Agathokleous, Rafaela; Karellas, Sotirios (My University, 2017)
In building-integrated photovoltaic (BIPV) systems, PV panels and the façade or roof of the building are separated with an air gap, with openings in the bottom and top, to circulate the air and cool the PV panels to avoid efficiency loss and increase of the building’s cooling loads in hot climates. The natural ventilation of the air gap has several advantages in comparison with the mechanical, such as the avoidance of the energy cost for the fan’s operation, noise, space requirement for the fan installation, maintenance. One of the most important parameters to be investigated in order to have a general view of the system’s performance prior or after the installation and avoid PVs and building’s overheating, is the air flow effect in the air gap, in terms of the convective heat transfer coefficients. In this study, a series of experiments on a custom made BIPV system were carried in real outside conditions as well as indoors with the use of a large scale solar simulator to measure the thermal characteristics of the system and its thermal behaviour. Indoor experiments were performed to avoid external disturbances from wind that occur outside. The experimental data are then used to estimate the convective heat transfer coefficients to fit the real conditions of the BIPV systems. Then two correlations are proposed for the estimation of the Nusselt number that fits best the thermal characteristics of a naturally ventilated BIPV system.
Keywords: Air duct; BIPV; Heat transfer coefficients; Natural convection; Solar Simulator